Amino Acid and Proliferation PET/CT for the Diagnosis of Multiple Myeloma - Minamimoto, Ryogo (Frontiers in Nuclear Medicine, 2022)
Multiple myeloma (MM) is a hematologic malignancy characterized by infiltration of monoclonal plasma cells in the bone marrow (BM). The standard examination performed for assessment of bone lesions has progressed from radiographic skeletal survey to the more advanced imaging modalities of computed tomography (CT), magnetic resonance imaging (MRI), and positron emission tomography/computed tomography (PET/CT). The Durie–Salmon PLUS staging system (upgraded from the Durie–Salmon staging system) applies 2-[18F]-fluoro-2-deoxy-glucose (18F-FDG) PET/CT and MRI findings to the staging of MM, and 18F-FDG PET/CT has been incorporated into the International Myeloma Working Group (IMWG) guidelines for the diagnosis and staging of MM. However, 18F-FDG PET/CT has significant limitations in the assessment of diffuse bone marrow infiltration and in differentiation of MM lesions from inflammatory or infectious lesions. The potential of several new PET tracers that exploit the underlying disease mechanism of MM has been evaluated in terms of improving the diagnosis. L-type amino acid transporter 1 (LAT1) is a membrane protein that transports neutral amino acids and is associated with cell proliferation, and has strong ability to represent the status of MM. This review evaluates the potential of amino acid and proliferation PET tracers for diagnosis and compares the characteristics and accuracy of non-FDG tracers in the management of patients with multiple myeloma.